Gut–Adipose Tissue Axis and Metabolic Health - Sanja Borozan; Cornelius J. Fernandez; Adnan Samee; Joseph M. Pappachan (Current Issues in Molecular Biology)
The gut–adipose tissue axis plays a crucial role in metabolic health. It is a two-way communication pathway between the gastrointestinal tract and adipose tissue. This axis influences physiological processes vital for maintaining metabolic health, including energy homeostasis, lipid metabolism, and inflammation. Emerging research suggests that the gut microbiota, composed of trillions of microorganisms residing in the intestines, significantly impacts this axis by modulating host metabolism. An imbalance in the gut microbiota (dysbiosis) has been linked to obesity, insulin resistance, and other metabolic disorders. Innovative therapeutic strategies and dietary interventions aimed at modulating the gut–adipose tissue axis have shown encouraging results in improving metabolic health. A deeper critical understanding of the gut–adipose tissue axis is, therefore, essential in understanding the pathophysiology of metabolic disorders so that targeted interventions can be developed to prevent and treat these metabolic disorders. This article highlights the need for integrative approaches that consider both gastrointestinal and adipose functions in metabolic health management.